GRADE guidelines: 9. Rating up the quality of evidence. - Guyatt, G; Oxman, A; Sultan, S; Glasziou, P; Akl, E; Alonso-Coello, P; Atkins, D; Kunz, R; Brozek, J; Montori, V; Jaeschke, R; Rind, D; et al. (2011)
The most common reason for rating up the quality of evidence is a large effect. GRADE suggests considering rating up quality of evidence one level when methodologically rigorous observational studies show at least a two-fold reduction or increase in risk, and rating up two levels for at least a five-fold reduction or increase in risk. Systematic review authors and guideline developers may also consider rating up quality of evidence when a dose-response gradient is present, and when all plausible confounders or biases would decrease an apparent treatment effect, or would create a spurious effect when results suggest no effect. Other considerations include the rapidity of the response, the underlying trajectory of the condition, and indirect evidence.